Shuttling of Rydberg Ions for Fast Entangling Operations - Vogel, J.; Li, W.; Mokhberi, A.; Lesanovsky,; Schmidt-Kaler, F. (Physical Review Letters, 2019)
We introduce a scheme to entangle Rydberg ions in a linear ion crystal, using the high electric polarizability of the Rydberg electronic states in combination with mutual Coulomb coupling of ions that establishes common modes of motion. After laser initialization of ions to a superposition of ground and Rydberg states, the entanglement operation is driven purely by applying a voltage pulse that shuttles the ion crystal back and forth. This operation can achieve entanglement on a sub-μs timescale, more than 2 orders of magnitude faster than typical gate operations driven by continuous-wave lasers. Our analysis shows that the fidelity achieved with this protocol can exceed 99.9% with experimentally achievable parameters.
CRIS-Team Scopus Importer:2023-03-27